Overcoming public resistance to carbon taxes. (6th June 2018) - Carattini, Stefano; Carvalho, Maria; Fankhauser, Sam
Abstract : Carbon taxes represent a cost‐effective way to steer the economy toward a greener future. In the real world, their application has however been limited. In this paper, we address one of the main obstacles to carbon taxes: public opposition. We identify drivers of and barriers to public support, and, under the form of stylized facts, provide general lessons on the acceptability of carbon taxes. We derive our lessons from a growing literature, as well as from a combination of policy "failures" and "successes." Based on our stylized facts, we formulate a set of suggestions concerning the design of carbon taxes. We consider the use of trial periods, tax escalators, environmental earmarking, lump‐sum transfers, tax rebates, and advanced communication strategies, among others. This paper contributes to the policy debate about carbon taxes, hopefully leading to more success stories and fewer policy failures. This article is categorized under: Climate Economics > Economics of Mitigation